Leadership Lens on Artificial Intelligence: How School Leaders Leverage AI for Efficiency, Development, and Change - Recamara, Isagani (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the extent of Artificial Intelligence (AI) integration in educational leadership practices among school heads in basic education schools in Dapitan City. It aimed to determine how AI is utilized across six leadership domains: administrative efficiency, instructional leadership support, data-driven decision-making, professional development and capacity-building, ethical and responsible AI governance, and innovation and change management. The study was anchored on established leadership perspectives emphasizing instructional leadership, data-informed decision-making, transformational leadership, and ethical leadership as conceptual foundations for understanding AI-enabled school leadership. A descriptive–quantitative research design was employed. Data were gathered using a structured survey questionnaire based on a validated technology leadership framework and adapted to reflect AI integration in school leadership functions. The respondents were school heads from basic education institutions in Dapitan City, who are directly responsible for instructional supervision, policy implementation, and school management. Descriptive statistics, specifically mean and standard deviation, were used to analyze the extent of AI integration across the identified domains. Findings revealed that AI is integrated into school leadership practices to a “Great Extent,” with an overall mean of 3.23. The highest level of integration was observed in administrative efficiency (3.27) and data-driven decision-making (3.26), both interpreted as “Very Great Extent,” indicating strong utilization of AI in operational management and analytical decision support. Instructional leadership support (3.20), professional development and capacity-building (3.22), ethical and responsible AI governance (3.20), and innovation and change management (3.20) were all interpreted as “Great Extent,” reflecting moderate but developing integration in pedagogical, developmental, and governance-related functions. Overall, results indicate that AI adoption in school leadership is progressing from operational efficiency toward broader strategic and instructional integration. The study concludes that while AI is substantially embedded in school leadership practices, its full transformative potential has not yet been maximized, particularly in instructional and governance domains. Strengthening digital leadership competencies, structured policy frameworks, and institutional support systems is recommended to enhance responsible and effective AI integration. In terms of sustainability, the study aligns with SDG 4 (Quality Education) by promoting improved educational leadership and institutional effectiveness through AI adoption. It also supports SDG 9 (Industry, Innovation and Infrastructure) by advancing digital transformation in school systems, and SDG 16 (Peace, Justice, and Strong Institutions) by emphasizing ethical governance, transparency, and accountability in technology use. From a sustainability perspective, the findings highlight institutional and governance sustainability by encouraging responsible AI integration that strengthens school management systems and leadership capacity. It also supports socio-technical sustainability by promoting balanced adoption of emerging technologies that enhance efficiency while ensuring ethical and human-centered decision-making in education.
Keywords: Administrative Efficiency; Artificial Intelligence; Data-Driven Decision-Making; Digital Leadership; Educational Leadership; Innovation and Change Management; Instructional Leadership; Professional Development; School Heads; Technology Integration